Self-adhesive high-thermal-conductivity self-leveling flame-retardant organic silicon pouring sealant and preparation method thereof

By chemically modifying the surface of thermally conductive inorganic filler particles and designing and synthesizing a specific structure of tackifier, the thermally conductive organic silicone potting adhesive is solved, and high thermal conductivity, low viscosity, self-leveling, excellent adhesiveness and flame retardancy are achieved.

CN119684964APending Publication Date: 2025-03-25CHINA BLUESTAR CHENGRAND CO LTD +1

Patent Information

Application Number
CN202311240117.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing thermally conductive silicone potting glue has a low thermal conductivity and high viscosity, making it difficult to meet the requirements of high heat dissipation in industries such as new energy vehicle electronic control systems, motor systems, battery systems and 5G communication base station systems. At the same time, there are settlement problems and insufficient adhesiveness.

Method used

The surface of thermally conductive inorganic filler particles is chemically modified by using filler surface treatment agents of specific structures to reduce interface thermal resistance and improve thermal conductivity; the viscosity-enhancing agents of specific structures are designed and synthesized to enhance bonding and anti-settlement properties, and coordinated with aluminum hydroxide to improve flame retardant efficiency.

Benefits of technology

It realizes high thermal conductivity, low viscosity, self-leveling and self-buffering properties of thermally conductive potting adhesives, excellent self-adhesion, flame retardant and electrical insulation, and is suitable for potting, sealing and bonding packaging of electronic components with high thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_60
    Figure SMS_60
  • Figure SMS_64
    Figure SMS_64
  • Figure SMS_74
    Figure SMS_74
Patent Text Reader

Abstract

The invention discloses a self-adhesive high-thermal-conductivity self-leveling flame-retardant organic silicon pouring sealant and a preparation method thereof. The pouring sealant is composed of a component A and a component B in parts by mass, wherein the component A comprises 1000-1400 parts of heat-conducting filler, 50-70 parts of vinyl-terminated silicone oil, 10-30 parts of vinyl-side silicone oil, 2-14 parts of filler surface treating agent, 5-14 parts of tackifier, 1-3 parts of pigment and 1-5 parts of platinum catalyst; the component B comprises the following components in parts by weight: 1000-1400 parts of heat-conducting filler, 60-80 parts of vinyl-terminated silicone oil, 5-10 parts of hydrogen-terminated silicone oil, 3-7 parts of hydrogen-terminated silicone oil, 2-14 parts of filler surface treating agent, 5-14 parts of tackifier and 1-5 parts of inhibitor; the component A and the component B are uniformly mixed according to the mass ratio of 1: 1 for use. The organic silicon pouring sealant prepared by the invention not only has excellent bonding performance with a base material, but also has a heat conductivity coefficient as high as 4.18 W / (m.K), low viscosity, good self-leveling property, good self-foam-discharging property, excellent constructability, flame retardance and electrical insulating property, and is suitable for pouring, sealing and bonding packaging of electronic components with higher heat conduction requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal conductive silicone materials, and specifically relates to a self-adhesive high thermal conductive self-leveling flame retardant silicone potting adhesive and a preparation method thereof. Background Art

[0002] Addition-type thermal conductive silicone potting adhesive has unique advantages, such as excellent weather resistance, high and low temperature resistance and electrical insulation, low internal stress, low curing shrinkage, good deep curing, no release of small molecules, and easy control of cross-linking density and curing speed. When used for potting of electronic components, it can make the internal components and circuits have good resistance to external impact and vibration, avoid direct exposure of internal components and circuits, improve the waterproof, moisture-proof, dust-proof, corrosion-resistant, heat dissipation and insulation properties of electronic devices, and ensure the performance and stable parameters of electronic components when working.

[0003] With the rapid development of the electronics industry and 5G communications, the density, power and integration of electronic devices are getting higher and higher, and the heat generated during operation has also doubled, which puts higher requirements on the thermal conductivity of thermal conductive potting glue. However, the thermal conductivity of thermal conductive silicone potting glue products on the market is low (only 0.6~2.7W / (m·K)) and the viscosity is high. It is difficult to meet the high heat dissipation requirements of silicone potting glue in the rapidly developing new energy vehicle electronic control system, motor system and battery system, and 5G communication base station system. The method of increasing the filling amount of thermal conductive filler is usually used to increase the thermal conductivity of silicone potting glue. However, increasing the filling amount will inevitably cause the viscosity of the potting glue to increase, the self-leveling and self-draining properties to deteriorate, and the operation and construction processability to deteriorate. To reduce the viscosity of the potting glue, silane coupling agents are usually used to modify the surface of the thermal conductive inorganic filler, but these silane coupling agents have weak binding force and poor coating on the surface of the inorganic filler particles, and their treatment effect is very limited. For example, CN115141223A uses a short-chain silane coupling agent to modify the surface of the thermally conductive filler, thereby reducing the viscosity of the potting compound and improving the fluidity. However, the invention is only used to prepare a potting compound with a conventional thermal conductivity (2.0 W / (m·K)).

[0004] The viscosity of the potting compound is reduced by modifying the surface of the thermal conductive filler with a surface treatment agent. The viscosity reduction may aggravate the sedimentation problem of the potting compound, that is, oil-powder separation occurs, and the bottom agglomeration and other undesirable phenomena occur, so that the construction process requirements of the potting compound cannot be met, and the thermal conductivity, mechanical properties and electrical properties of the product are affected. In order to solve the problem of filler sedimentation, an anti-settling agent is usually added to produce a similar "thixotropic" effect, promote the dispersion of thermal conductive filler particles in silicone oil, prevent the filler from agglomerating and sinking and agglomerating, and improve the sedimentation and agglomeration of the potting compound during storage and transportation to improve the stability of the potting compound. CN102675882A discloses an addition-type thermal conductive anti-settling silicone rubber and a preparation method thereof. The anti-settling agent is prepared by blending vinyl silicone oil, fumed silica, hexamethyldisilazane, and distilled water dehydration. The obtained thermal conductive silicone rubber has excellent flow properties and is easy to use, but silica will slowly produce a "structuring" phenomenon in the silicone rubber, causing the viscosity to increase continuously, which will affect the leveling of the potting compound. CN110484025A discloses a method for improving the anti-settling property and dispersibility of silicon micropowder in organic silicon potting glue, which improves the anti-settling property of silicon micropowder through the intermolecular force between the alkane chain segment and the ester group on the surface treatment agent. This method is limited to the thermal conductive potting glue with a low proportion of thermal conductive filler (150-300 parts) and a low thermal conductivity (<1.05W / (m·K)). CN113698609A discloses a polysiloxane terephthalate ester compound as an anti-settling agent, which is synthesized by a two-step method of esterification reaction and hydrosilylation reaction. This method is also limited to the anti-settling of thermal conductive potting glue with low thermal conductivity (<0.88W / (m·K)). CN114276502A discloses the preparation and application of an anti-settling agent for heat-conductive silicone potting glue. The polymer anti-settling agent is synthesized by a three-step method of acid-alcohol condensation reaction, hydrosilylation reaction, and atom transfer polymerization. The synthesis steps are complicated, and the prepared macromolecular anti-settling agent easily causes obvious thixotropy of the potting glue, affecting its leveling and self-draining properties.

[0005] Thermally conductive potting glue needs to have good adhesion to the substrate during sealing and packaging, which is usually achieved by pre-priming the substrate or adding a tackifier. The use of a primer will increase the operating procedures and reduce production efficiency, and the primer contains flammable organic solvents and hazardous chemicals, which increases the danger during storage, transportation and use. Adding a tackifier to addition-type silicone rubber to achieve the adhesion of the potting glue to the substrate can well avoid the problems caused by the primer, but it is necessary to design and synthesize a tackifier with a specific structure to achieve good adhesion. CN102408869A discloses an addition-type silicone potting glue for halogen-free flame-retardant electronic appliances, and its adhesion promoter contains amino groups, which are easy to poison the platinum catalyst and affect the product quality of the thermally conductive potting glue. CN106947428A discloses a two-component silicone potting glue and a preparation method thereof, wherein the tackifier is a polycyclic siloxane containing a nitrogen heterocycle, which will not cause poisoning of the platinum catalyst, but the tackifier has a relatively special structure and is very complicated to synthesize, which is not suitable for industrial production applications.

[0006] In addition, the thermally conductive potting compound also needs to have excellent flame retardancy. Current research reports are still mainly focused on the single performance of silicone potting compounds. The thermally conductive silicone potting compounds on the market have not yet taken into account multiple properties (such as high thermal conductivity, low viscosity, self-leveling, anti-settling, self-adhesion, and flame retardancy). Therefore, it is very necessary and urgent to develop a silicone potting compound that has high thermal conductivity, low viscosity, self-leveling, self-draining, anti-settling, self-adhesion, and flame retardancy. Summary of the invention

[0007] In view of the above technical problems, the present invention provides a self-adhesive, highly thermally conductive, self-leveling, flame-retardant silicone potting glue and a preparation method thereof. A filler surface treatment agent with a specific structure is used to chemically modify the surface of the thermally conductive inorganic filler particles, effectively improving the interface compatibility between the inorganic filler and the silicone oil and reducing the interface thermal resistance, thereby reducing the viscosity of the thermally conductive potting glue and improving the thermal conductivity. The thermally conductive potting glue with a lower viscosity has excellent self-leveling and self-foaming properties; one end of the molecular chain of the filler surface treatment agent contains an ester group, and the interaction between the ester groups can effectively avoid the hard sedimentation and agglomeration problems of the thermally conductive filler during the storage and transportation of the potting glue; a tackifier with a specific structure is designed and synthesized, and when added to the thermally conductive potting glue, it can give the material and the substrate excellent bonding properties, and cooperate with aluminum hydroxide to improve the flame retardant efficiency. The ester groups and other groups contained in the tackifier can also enhance the anti-sedimentation performance of the thermally conductive potting glue, and will not affect the fluidity of the potting glue and will not cause platinum catalyst poisoning. The prepared thermal conductive potting adhesive has the characteristics of high thermal conductivity, low viscosity, good self-leveling and self-draining properties, as well as excellent self-adhesion, flame retardancy and electrical insulation.

[0008] The purpose of the present invention is achieved through the following technical solutions: A self-adhesive, highly thermally conductive, self-leveling, flame-retardant silicone potting adhesive, comprising the following components A and B in parts by mass: Component A: 1000-1400 parts of thermal conductive filler, 50-70 parts of terminal vinyl silicone oil, 10-30 parts of side vinyl silicone oil, 2-14 parts of filler surface treatment agent, 5-14 parts of tackifier, 1-3 parts of colorant, 1-5 parts of platinum catalyst; Component B: 1000-1400 parts of thermal conductive filler, 60-80 parts of vinyl-terminated silicone oil, 5-10 parts of hydrogen-terminated silicone oil, 3-7 parts of hydrogen-terminated silicone oil, 2-14 parts of filler surface treatment agent, 5-14 parts of tackifier, 1-5 parts of inhibitor; The component A and the component B are mixed evenly in a mass ratio of 1:1 for use.

[0009] In the present invention, the thermal conductive filler is a material having a median particle size of 40 to 80 Spherical alumina, median particle size 6 to 20 Spherical alumina, median particle size 1 to 2 Spherical alumina and median particle size 1 to 5 The aluminum hydroxide is compounded in a mass ratio of 40-80: 20-40: 10-20: 10-20.

[0010] The vinyl-terminated silicone oil is double-terminated vinyl polydimethylsiloxane with a viscosity of 60 to 300 mPa·s.

[0011] The side vinyl silicone oil is polydimethylmethylvinylsiloxane, with a viscosity of 50 to 200 mPa.s and a vinyl mass content of 3 to 8%.

[0012] The hydrogen-terminated silicone oil is double-terminal hydrogen-terminated polydimethylsiloxane with a viscosity of 70 to 200 mPa.s.

[0013] The side hydrogen-containing silicone oil is polydimethylmethylhydrogensiloxane, with a viscosity of 30 to 260 mPa.s and a hydrogen mass content of 0.15 to 1%.

[0014] The colorant is one or more of black paste, blue paste, yellow paste, pink paste or red paste.

[0015] The platinum catalyst is a platinum-alcohol complex or a platinum-vinylsiloxane complex, wherein the effective content of platinum atoms is 2000-10000 ppm.

[0016] The inhibitor is one or more of 1-ethynyl-1-cyclohexanol, 3,5-dimethyl-1-hexyn-3-ol, 4-phenyl-3-butyn-2-ol, 2-methyl-3-butyn-2-ol, diallyl maleate, tetramethyltetravinylcyclotetrasiloxane, and polydivinyltetramethyldisiloxane.

[0017] In the present invention, the filler surface treatment agent has a structure as shown in formula (I): Formula (I) In the above formula (I), R1 is , , , , One of; R2 is one of methyl, methoxy and ethoxy; R3 is methyl or ethyl; R4 is one of methyl, methoxy and ethoxy; In formula (I), n=10 to 200 and is an integer.

[0018] The filler surface treatment agent is prepared by the following method, and the specific steps are as follows: A. Add hexamethylcyclotrisiloxane monomer, initiator and toluene into a reaction bottle and mix well, add toluene solution of organic base, and stir at room temperature for polymerization reaction for 1 to 6 hours under nitrogen atmosphere; B. Add chlorosilane and acid binding agent to the system after polymerization in step A to carry out end-capping reaction, continue stirring for 1 to 20 hours under nitrogen atmosphere, and then remove the precipitate and filter to obtain the filler surface treatment agent.

[0019] In step A, The initiator is any substance with the following structural formula: , , , , .

[0020] The organic base is selected from any one of the following substances: , , , , , , , .

[0021] Furthermore, the molar ratio of the hexamethylcyclotrisiloxane monomer to the initiator is 3:1 to 50:1.

[0022] In step B, The chlorosilane is selected from any one of the following substances: , , , .

[0023] The acid binding agent is selected from one or more of triethylamine, pyridine and N,N-diisopropylethylamine.

[0024] In the present invention, the tackifier has a structure as shown in formula (II): Formula (II) In the above formula (II), R1, R2, and R3 are any of the following substances: , , , , , , , , , , , , , , or .

[0025] The tackifier is synthesized by hydrosilylation reaction, Michael addition reaction and phosphine hydrogen addition reaction, and the specific steps are as follows: Step 1: pentaerythritol tetraacrylate and a silicon hydrogen compound and a platinum catalyst supported on an alumina carrier are uniformly mixed, and reacted at 80° C. for 5 hours. After the reaction is completed, the mixture is cooled to room temperature, and the supported platinum catalyst is removed by suction to obtain an intermediate compound; Step 2: After the intermediate compound is uniformly mixed with mercaptosilane coupling agent, aminosilane coupling agent, diphenylphosphine and toluene, the mixture is reacted at 40° C. for 12 hours. After the reaction is completed, the mixture is cooled to room temperature and low-boiling substances are removed by vacuum distillation to obtain a tackifier.

[0026] In step 1, The silicon-hydrogen compound is any substance having the following structure: , , , , , , , , .

[0027] The mass content of platinum atoms in the platinum catalyst supported on the alumina carrier in the reaction system of step 1 is 4 to 25 ppm.

[0028] In step 2, The mercaptosilane coupling agent is any one or two substances having the following structures: , .

[0029] The aminosilane coupling agent is any one or more substances having the following structures: , , , .

[0030] Furthermore, the molar ratio of the pentaerythritol tetraacrylate to the silicon-hydrogen compound, the mercaptosilane coupling agent, the aminosilane coupling agent, and the diphenylphosphine is 1: 1-2.7: 0.1-1: 0.1-1: 0.1-0.5.

[0031] The present invention also provides a method for preparing a self-adhesive, highly thermally conductive, self-leveling, flame-retardant organic silicone potting adhesive, comprising the following steps: (1) Preparation of component A: Add end vinyl silicone oil, side vinyl silicone oil and filler surface treatment agent into a double planetary power mixer and mix and disperse them evenly, then add thermal conductive filler and stir and disperse them for 2 to 5 hours, then heat to 110 to 140°C under stirring, vacuum and stir for 1 to 2 hours, the vacuum degree is -0.09 MPa, cool to room temperature and fill with nitrogen to break the vacuum to obtain base rubber A; then add tackifier, colorant and platinum catalyst, stir and mix at room temperature for 20 to 60 minutes, and degas for 20 minutes to obtain component A; (2) Preparation of component B: Add end vinyl silicone oil and filler surface treatment agent into a dual planetary power mixer and mix and disperse them evenly, then add thermal conductive filler and stir and disperse them for 2 to 5 hours, then heat to 110 to 140°C while stirring, and stir under vacuum for 1 to 2 hours with a vacuum degree of -0.09 MPa. Cool to room temperature and fill with nitrogen to break the vacuum to obtain base rubber B; then add end hydrogen silicone oil, side hydrogen silicone oil, tackifier and inhibitor, stir and mix at room temperature for 20 to 60 minutes, and degas for 20 minutes to obtain component B.

[0032] The beneficial effects of the present invention are: 1. In the present invention, a filler surface treatment agent having a specific structure as shown in formula (I) is used to perform in-situ chemical modification on the surface of the thermally conductive inorganic filler particles, and an organic polysiloxane molecular chain is grafted on the surface of the inorganic filler particles, thereby effectively improving the compatibility between the inorganic filler and the silicone oil matrix, increasing the filling amount and dispersibility of the filler in the silicone oil, reducing the viscosity of the thermally conductive silicone potting glue and the interface thermal resistance between the filler and the silicone oil matrix, improving the thermal conductivity of the potting glue, and meeting the construction performance requirements of the thermally conductive potting glue such as self-leveling and self-draining; one end of the molecular chain of the filler surface treatment agent contains an ester group, and the interaction force between the ester groups can effectively avoid the hard sedimentation and agglomeration problems of the inorganic filler during the storage and transportation of the thermally conductive potting glue.

[0033] 2. In the present invention, a tackifier having a special structure as shown in formula (II) is designed and synthesized, and added to the thermally conductive silicone potting glue, which can achieve excellent, stable and reliable bonding between the thermally conductive potting glue and the substrate (copper, aluminum, nickel, gold, epoxy resin, PC, etc.); a small amount of tertiary amine and phosphorus-containing substances contained in the tackifier structure can cooperate with aluminum hydroxide filler to improve the flame retardant efficiency, and experiments have verified that it will not cause platinum catalyst poisoning; the ester group and other groups contained in the tackifier molecules can further enhance the anti-sedimentation performance of the thermally conductive potting glue, and will not affect the fluidity of the potting glue.

[0034] 3. The synthesis method of the tackifier of the present invention is novel, simple and efficient, uses conventional industrial raw materials, has no potential major risks in the synthesis process, and is suitable for industrial-scale production and preparation.

[0035] Fourth, the organic silicone potting glue prepared by the present invention not only has excellent bonding performance with the substrate, but also has a thermal conductivity of up to 4.18W / (m·K), a minimum viscosity of up to 21900mPa·s, good self-leveling and self-draining properties, good anti-settling properties, excellent construction properties, flame retardancy and electrical insulation, showing very excellent comprehensive performance, and is very suitable for electronic component potting, sealing, bonding and packaging purposes with high thermal conductivity requirements. In addition, the preparation method and process are simple and controllable, and easy to mass-produce. DETAILED DESCRIPTION

[0036] In order to better explain the present invention, the present invention is specifically described below in conjunction with embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the contents of the present invention still belong to the scope of protection of the present invention.

[0037] The following four silicone oils were used in the following examples, as follows: The vinyl-terminated silicone oil is double-terminated vinyl polydimethylsiloxane with a viscosity of 60 to 300 mPa·s; The side vinyl silicone oil is polydimethylmethylvinylsiloxane, with a viscosity of 50 to 200 mPa.s and a vinyl mass content of 3 to 8%; The hydrogen-terminated silicone oil is double-terminated hydrogen-terminated polydimethylsiloxane with a viscosity of 70 to 200 mPa.s; The side hydrogen-containing silicone oil is polydimethylmethylhydrogensiloxane, with a viscosity of 30 to 260 mPa.s and a hydrogen content of 0.15 to 1%.

[0038] Example 1 A self-adhesive, highly thermally conductive, self-leveling, flame-retardant silicone potting adhesive is composed of the following components A and B in parts by mass, wherein the components A and B are uniformly mixed in a mass ratio of 1:1 for use.

[0039] Preparation of component A: 60 parts of end-vinyl silicone oil (viscosity of 150 mPa.s), 21 parts of side-vinyl silicone oil [viscosity of 100 mPa.s, vinyl content (mass fraction) of 5%) and 6 parts of filler surface treatment agent are added into a double planetary power mixer and mixed and dispersed evenly, and then a thermal conductive filler is added and stirred and dispersed for 4 hours, and then the temperature is raised to 120°C under stirring, and vacuum stirring is performed for 1.5 hours, and the vacuum degree is -0.09 MPa, and the base rubber A is obtained by cooling to room temperature and filling with nitrogen to break the vacuum; then 8 parts of tackifier, 2 parts of black paste and 3 parts of platinum catalyst (platinum-vinyl siloxane complex with an effective content of platinum atoms of 10000 ppm) are added, and the mixture is stirred and mixed at room temperature for 30 minutes, and then deaerated for 20 minutes to obtain component A; Preparation of component B: Add 74 parts of terminal vinyl silicone oil (viscosity of 150mPa.s) and 6 parts of filler surface treatment agent into a double planetary power mixer and mix and disperse evenly, then add thermal conductive filler and stir and disperse for 4 hours, then heat to 120°C under stirring, vacuum and stir for 1.5 hours, the vacuum degree is -0.09MPa, cool to room temperature and fill with nitrogen to break the vacuum to obtain base rubber B; then add 5 parts of terminal hydrogen-containing silicone oil (viscosity of 90mPa.s), 5 parts of side hydrogen-containing silicone oil [viscosity of 60mPa.s, hydrogen content (mass fraction) of 0.4%], 8 parts of thickener and 2 parts of inhibitor (1-ethynyl-1-cyclohexanol), stir and mix at room temperature for 30 minutes, and degas for 20 minutes to obtain component B.

[0040] Among the above components, The thermal conductive filler is compounded by 600 parts of spherical alumina with a median particle size of 60µm, 400 parts of spherical alumina with a median particle size of 15µm, 150 parts of spherical alumina with a median particle size of 1.5µm and 200 parts of aluminum hydroxide with a median particle size of 2µm.

[0041] The structural formula of the filler surface treatment agent is as follows: The filler surface treatment agent is prepared by the following method, and the specific steps are as follows: A. Add 500g (2.25mol) hexamethylcyclotrisiloxane, 21.63g (135.0mmol) initiator and 260mL toluene into a three-necked flask, and blow nitrogen into the system while the raw monomers are dissolved. Add a tetrahydrofuran solution of an organic base (0.1g / mL, 13.79mL, 9mmol) into the three-necked flask, and stir the polymerization reaction at room temperature for 1h.

[0042] B. Add chlorosilane (42.29 g, 270 mmol) and triethylamine (28.69 g, 283.5 mmol) as an acid binding agent to the reaction system for end-capping reaction, and continue stirring at room temperature for 16 hours. After the reaction is completed, the reaction mixture is concentrated under reduced pressure to remove low-boiling substances such as solvents, and then filtered to remove insoluble salts to obtain 497 g of clear and transparent oily liquid, that is, filler surface treatment agent 1.

[0043] Further, The initiator is ; Organic base is ; Chlorosilane is .

[0044] Among the above components, The structural formula of the tackifier is as follows: Among them, R1, R2, and R3 are , , , and .

[0045] The tackifier is synthesized by hydrosilylation reaction, Michael addition reaction and phosphine hydrogen addition reaction, and the specific steps are as follows: Step 1: 100 g (0.284 mol) of pentaerythritol tetraacrylate, 105.27 g (0.568 mol) of a silicon-hydrogen compound, and 0.56 g of a platinum catalyst supported on an alumina carrier (the amount of platinum atoms in the reaction system is 10 ppm) were mixed evenly, and reacted at 80° C. for 5 h. After the reaction was completed, the mixture was cooled to room temperature, and the supported platinum catalyst was removed by suction to obtain an intermediate compound 1; Step 2: The intermediate compound 1 was mixed evenly with 18.59 g (94.6 mmol) of mercaptosilane coupling agent, 18.28 g (94.6 mmol) of aminosilane coupling agent, 19.12 g (94.6 mmol) of diphenylphosphine and 40 mL of toluene, and reacted at 40°C for 12 h. After the reaction was completed, the mixture was cooled to room temperature and low-boiling substances such as the solvent were removed by distillation under reduced pressure to obtain the thickener 1.

[0046] Further, Silicon-hydrogen compounds are and 1:1 mixture; Mercaptosilane coupling agent is ; Aminosilane coupling agent is .

[0047] The thermally conductive silicone encapsulant before and after curing was subjected to relevant performance tests (including viscosity, hardness, thermal conductivity, bonding shear strength, breakdown voltage strength, volume resistivity, flame retardant grade, self-leveling and anti-settling properties, etc.), and the results are shown in Table 1.

[0048] Example 2 A self-adhesive, highly thermally conductive, self-leveling, flame-retardant silicone potting adhesive is composed of the following components A and B in parts by mass, wherein the components A and B are uniformly mixed in a mass ratio of 1:1 for use.

[0049] Preparation of component A: 70 parts of end-vinyl silicone oil (viscosity of 120 mPa.s), 10 parts of side-vinyl silicone oil [viscosity of 150 mPa.s, vinyl content (mass fraction) of 6%) and 6.5 parts of filler surface treatment agent are added into a double planetary power mixer and mixed and dispersed evenly, and then a thermal conductive filler is added and stirred and dispersed for 3 hours, and then the temperature is raised to 120°C under stirring, and vacuumed and stirred for 1 hour, the vacuum degree is -0.09 MPa, and cooled to room temperature and filled with nitrogen to break the vacuum to obtain base glue A; then 7.5 parts of tackifier, 2 parts of blue paste and 4 parts of platinum catalyst (platinum-vinyl siloxane complex with an effective content of platinum atoms of 7500 ppm) are added, and the mixture is stirred and mixed at room temperature for 30 minutes, and deaerated for 20 minutes to obtain component A; Preparation of component B: Add 75 parts of end vinyl silicone oil (viscosity of 120mPa.s) and 6.5 parts of filler surface treatment agent into a double planetary power mixer and mix and disperse evenly, then add thermal conductive filler and stir and disperse for 3h, then heat to 120℃ under stirring, vacuum and stir for 1h, the vacuum degree is -0.09MPa, cool to room temperature and fill with nitrogen to break the vacuum to obtain base rubber B; then add 5 parts of end hydrogen silicone oil (viscosity of 100mPa.s), 4 parts of side hydrogen silicone oil [viscosity of 90mPa.s, hydrogen content (mass fraction) of 0.5%], 7.5 parts of thickener and 2 parts of inhibitor (diallyl maleate), stir and mix at room temperature for 30min, and degas for 20min to obtain component B.

[0050] Among the above components, The thermal conductive filler is compounded by 700 parts of spherical alumina with a median particle size of 70µm, 300 parts of spherical alumina with a median particle size of 12µm, 100 parts of spherical alumina with a median particle size of 1.5µm and 200 parts of aluminum hydroxide with a median particle size of 3µm.

[0051] The structural formula of the filler surface treatment agent is as follows: The filler surface treatment agent is prepared by the following method, and the specific steps are as follows: A. Add 500g (2.25mol) hexamethylcyclotrisiloxane, 45.52g (225.0mmol) initiator and 270mL toluene into a three-necked flask, and blow nitrogen into the system while the raw monomers are dissolved. Add a tetrahydrofuran solution of an organic base (0.1g / mL, 17.13mL, 11.25mmol) into the three-necked flask, and stir the polymerization reaction at room temperature for 2h.

[0052] B. Add chlorosilane (80.48 g, 405 mmol) and triethylamine (43.03 g, 425.25 mmol) as an acid binding agent to the reaction system for end-capping reaction, and continue stirring at room temperature for 12 hours. After the reaction is completed, the reaction mixture is concentrated under reduced pressure to remove low-boiling substances such as solvents, and then filtered to remove insoluble salts to obtain 525 g of clear and transparent oily liquid, that is, filler surface treatment agent 2.

[0053] Further, The initiator is ; Organic base is ; Chlorosilane is .

[0054] Among the above components, The structural formula of the tackifier is as follows: Among them, R1, R2, and R3 are , , , and .

[0055] The tackifier is synthesized by hydrosilylation reaction, Michael addition reaction and phosphine hydrogen addition reaction, and the specific synthesis preparation steps are as follows: Step 1: 100 g (0.284 mol) of pentaerythritol tetraacrylate, 193.48 g (0.71 mol) of a silicon-hydrogen compound, and 0.84 g of a platinum catalyst supported on an alumina carrier (the amount of platinum atoms in the reaction system is 15 ppm) were mixed evenly, and reacted at 80° C. for 5 h. After the reaction was completed, the mixture was cooled to room temperature, and the supported platinum catalyst was removed by suction to obtain an intermediate compound 2; Step 2: The intermediate compound 2 was mixed evenly with 11.29 g (47.3 mmol) of mercaptosilane coupling agent, 11.13 g (47.3 mmol) of aminosilane coupling agent, 9.56 g (47.3 mmol) of diphenylphosphine and 30 mL of toluene, and reacted at 40°C for 12 h. After the reaction was completed, the mixture was cooled to room temperature and low-boiling substances such as the solvent were removed by distillation under reduced pressure to obtain the thickener 2.

[0056] Further, Silicon-hydrogen compounds are and 1:1 mixture; Mercaptosilane coupling agent is ; Aminosilane coupling agent is .

[0057] The thermally conductive silicone encapsulant before and after curing was subjected to relevant performance tests (including viscosity, hardness, thermal conductivity, bonding shear strength, breakdown voltage strength, volume resistivity, flame retardant grade, self-leveling and anti-settling properties, etc.), and the results are shown in Table 1.

[0058] Example 3 A self-adhesive, highly thermally conductive, self-leveling, flame-retardant silicone potting adhesive is composed of the following components A and B in parts by mass, wherein the components A and B are uniformly mixed in a mass ratio of 1:1 for use.

[0059] Preparation of component A: 66 parts of end-vinyl silicone oil (viscosity of 100 mPa.s), 15 parts of side-vinyl silicone oil [viscosity of 180 mPa.s, vinyl content (mass fraction) of 4%) and 8 parts of filler surface treatment agent were added to a double planetary power mixer and mixed and dispersed evenly, and then thermal conductive fillers (700 parts of spherical alumina with a median particle size of 70 um, 400 parts of spherical alumina with a median particle size of 20 um, 150 parts of spherical alumina with a median particle size of 2 um) were added. and 150 parts of aluminum hydroxide with a median particle size of 5um) were stirred and dispersed for 4 hours, then heated to 110°C under stirring, vacuumed and stirred for 1 hour, the vacuum degree was -0.09MPa, cooled to room temperature, filled with nitrogen to break the vacuum to obtain base rubber A; then 7 parts of tackifier, 2 parts of pink paste and 2 parts of platinum catalyst (platinum-alcohol complex with an effective content of platinum atoms of 10000ppm) were added, stirred and mixed at room temperature for 30 minutes, and degassed for 20 minutes to obtain component A; Preparation of component B: 74 parts of vinyl-terminated silicone oil (viscosity 100mPa.s) and 8 parts of filler surface treatment agent were added to a double planetary power mixer and mixed and dispersed evenly, and then thermal conductive fillers (700 parts of spherical alumina with a median particle size of 70um, 400 parts of spherical alumina with a median particle size of 20um, 150 parts of spherical alumina with a median particle size of 2um and 150 parts of aluminum hydroxide with a median particle size of 5um) were added and stirred and dispersed for 4 hours, and then The temperature was raised to 110°C, and vacuum stirring was performed for 1 hour, with a vacuum degree of -0.09 MPa. The mixture was cooled to room temperature and filled with nitrogen to break the vacuum to obtain base rubber B. Then 6 parts of end hydrogenated silicone oil (viscosity of 200 mPa.s), 3 parts of side hydrogenated silicone oil [viscosity of 45 mPa.s, hydrogen content (mass fraction) of 0.7%), 7 parts of thickener and 2 parts of inhibitor (polydivinyltetramethyldisiloxane) were added, and the mixture was stirred and mixed at room temperature for 30 minutes, and deaeration treatment was performed for 20 minutes to obtain component B.

[0060] Among the above components, The thermal conductive filler is compounded by 700 parts of spherical alumina with a median particle size of 70µm, 400 parts of spherical alumina with a median particle size of 20µm, 150 parts of spherical alumina with a median particle size of 2µm and 150 parts of aluminum hydroxide with a median particle size of 5µm.

[0061] The structural formula of the filler surface treatment agent is as follows: The filler surface treatment agent is prepared by the following method, and the specific steps are as follows: A. Add 500g (2.25mol) hexamethylcyclotrisiloxane, 17.24g (84.37mmol) initiator and 260mL toluene into a three-necked flask, and blow nitrogen into the system while the raw monomers are dissolved. Add a tetrahydrofuran solution of an organic base (0.1g / mL, 28.64mL, 8.4mmol) into the three-necked flask, and stir the polymerization reaction at room temperature for 1h.

[0062] B. Add chlorosilane (21.03 g, 168.74 mmol) and triethylamine (17.93 g, 177.18 mmol) as an acid binding agent to the reaction system for end-capping reaction, and continue stirring at room temperature for 16 hours. After the reaction is completed, the reaction mixture is concentrated under reduced pressure to remove low-boiling substances such as solvents, and then filtered to remove insoluble salts to obtain 480 g of clear and transparent oily liquid, that is, filler surface treatment agent 3.

[0063] Further, The initiator is ; Organic base is ; Chlorosilane is .

[0064] Among the above components, The structural formula of the tackifier is as follows: Among them, R1, R2, and R3 are , , , , and .

[0065] The tackifier is synthesized by hydrosilylation reaction, Michael addition reaction and phosphine hydrogen addition reaction, and the specific synthesis preparation steps are as follows: Step 1: 100 g (0.284 mol) of pentaerythritol tetraacrylate, 181.28 g (0.767 mol) of a silicon-hydrogen compound, and 0.84 g of a platinum catalyst supported on an alumina carrier (the amount of platinum atoms in the reaction system is 15 ppm) were mixed evenly, and reacted at 80° C. for 5 h. After the reaction was completed, the mixture was cooled to room temperature, and the supported platinum catalyst was removed by suction to obtain an intermediate compound 3; Step 2: The intermediate compound 3 was mixed evenly with 8.36 g (42.6 mmol) of mercaptosilane coupling agent, 9.70 g (28.4 mmol) of aminosilane coupling agent, 2.87 g (14.2 mmol) of diphenylphosphine and 20 mL of toluene, and reacted at 40°C for 12 h. After the reaction was completed, the mixture was cooled to room temperature and the solvent and other low-boiling substances were removed by distillation under reduced pressure to obtain thickener 3.

[0066] Further, Silicon-hydrogen compounds are , and 2:1:1 mixture; Mercaptosilane coupling agent is ; Aminosilane coupling agent is .

[0067] The thermally conductive silicone encapsulant before and after curing was subjected to relevant performance tests (including viscosity, hardness, thermal conductivity, bonding shear strength, breakdown voltage strength, volume resistivity, flame retardant grade, self-leveling and anti-settling properties, etc.), and the results are shown in Table 1.

[0068] Comparative Example 1 This comparative example is a comparison with Example 1, except that the surface treatment agent 1 in Example 1 is replaced with an equal amount of octadecyltrimethoxysilane, and other conditions are the same as those in Example 1.

[0069] Comparative Example 2 This comparative example is a comparison of Example 2, except that the surface treatment agent 2 in Example 2 is replaced by an equal amount of a mixture of dodecyltriethoxysilane and vinyltriethoxysilane (mass ratio is 50 / 1), and other conditions are the same as Example 2.

[0070] Comparative Example 3 This comparative example is a comparison with Example 3, except that the viscosity enhancer 3 in Example 3 is replaced by an equal weight ratio mixture of γ-glycidyloxypropyltrimethoxysilane (KH-560) and 3-(methacryloyloxy)propyltrimethoxysilane (KH-570), and other conditions are the same as those in Example 3.

[0071] The performance of the organosilicon potting adhesives prepared in the above Examples 1 to 3 and Comparative Examples 1 to 3 was tested.

[0072] 1. Viscosity test: Use GB / T 2794-2013 method to mix component A and component B in a mass ratio of 1 / 1 and then conduct viscosity test.

[0073] 2. Hardness test: Mix the thermally conductive silicone potting glue in a mass ratio of A / B = 1 / 1, pour it into 6mm thick molds, bake it in an 80℃ oven for 30 minutes, then cool it to room temperature, take out the sample, and test it using the GB / T 531.1-2008 method.

[0074] 3. Thermal conductivity test: Prepare test specimens according to the above method 2 and test using ASTM D5470 method.

[0075] 4. Shear strength test: Mix the thermally conductive silicone potting glue in a mass ratio of A / B = 1 / 1, apply it on the copper sheet (or aluminum sheet) respectively, bake it in an 80℃ oven for 30 minutes, then cool it to room temperature, take out the copper sheet (or aluminum sheet), and test it using the GB / T 7124-2008 method.

[0076] 5. Breakdown voltage strength and volume resistivity test: After mixing the thermal conductive silicone potting glue in a mass ratio of A / B = 1 / 1, pour it into 1mm thick molds respectively, bake it in an 80℃ oven for 30 minutes, then cool it to room temperature and take it out. Use GB / T 1695-2005 to test the breakdown voltage strength, and use GB / T 1692-2008 to test the volume resistivity.

[0077] 6. Flame retardant test: After mixing the thermally conductive silicone potting glue in a mass ratio of A / B = 1 / 1, pour it into 3mm thick molds respectively, bake it in an 80℃ oven for 30 minutes, then cool it to room temperature and take it out, and test it using ANSI / UL-94-1985.

[0078] 7. Self-leveling test: After the thermal conductive silicone potting glue is evenly mixed in a mass ratio of A / B = 1 / 1, the diameter of the self-leveling diffusion of the mixed glue after 1 minute is measured using a QCT thick paint putty consistency tester, and the average value of three tests is taken as the result.

[0079] 8. Self-degassing speed: After mixing the thermally conductive silicone potting glue in a mass ratio of A / B = 1 / 1, pour it into a 50mm×50mm container cavity and visually observe the self-degassing speed of the glue within 2 minutes.

[0080] 9. Anti-settling test: Take 100g of component B sample and place it in a 100mL graduated cylinder. After one month, measure the height of the oil layer on the surface of the rubber compound and stir the rubber compound with a glass rod to observe the agglomeration of the bottom filler.

[0081] 10. Performance test after heat aging: Prepare test specimens according to the above method 2, place them in an electric blast oven, and heat age them at 150°C for 1000h. Then take out the specimens and place them at room temperature for 24h. Use GB / T531.1-2008 method to test the hardness, and use ASTM D5470 method to test the thermal conductivity.

[0082] The relevant performance results are shown in Table 1.

[0083] From the data in Table 1, it can be seen that the self-adhesive high thermal conductivity self-leveling flame-retardant silicone potting glue prepared by using homemade special structure filler surface treatment agent and tackifier in Examples 1 to 3 of the present invention not only has a thermal conductivity of 4.12 W / (m·K), 4.05 W / (m·K), and 4.18 W / (m·K), but also has low viscosity, excellent self-adhesive performance, self-leveling, self-draining and anti-settling properties, and excellent comprehensive properties such as hardness, breakdown voltage strength, volume resistivity and flame retardancy. Therefore, the thermally conductive silicone potting glue prepared by the invention is very suitable for application scenarios of electronic component potting, sealing, and bonding packaging with high thermal conductivity requirements.

[0084] However, the silicone potting adhesive prepared by using conventional commercial silane coupling agents (octadecyltrimethoxysilane, dodecyltriethoxysilane and vinyltriethoxysilane) as filler surface treatment agents in Comparative Examples 1 and 2 has a significantly lower thermal conductivity, a significantly increased viscosity, and significantly lower self-leveling, self-degassing, anti-settling and self-adhesive properties than Examples 1 and 2, as well as an increase in thermal aging hardness and a significant decrease in thermal conductivity. This is because the chain segment of the filler surface treatment agent of the silane coupling agent is relatively short, and its modified filler effect is limited, and the compatibility between the inorganic filler and the polysiloxane cannot be well improved. After the silane coupling agent is grafted onto the filler particles, its interaction force is weak, and it cannot play a good anti-settling effect. In Comparative Example 3, a mixture of KH-560 and KH-570 was used to replace the homemade tackifier. Compared with Example 3, the self-adhesive performance of the prepared silicone potting compound was significantly reduced, and the anti-settling and flame retardancy were also reduced. This is because the conventional tackifier (mixture of KH-560 and KH-570) has limited tackifying effect in the silicone potting compound system, and the tackifier cannot play a good synergistic role in anti-settling and flame retardancy.

[0085] The embodiments described above are only preferred implementation modes of the present invention. The implementation modes of the present invention are not subject to any limitation of the embodiments described above. Therefore, any other modifications, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention should be regarded as equivalent replacement methods and are included in the protection scope of the technical solution of the present invention.

Claims

1. A self-adhesive, highly thermally conductive, self-leveling, flame-retardant silicone potting adhesive, characterized in that: The following components A and B are calculated by weight: composition: Component A: 1000-1400 parts of thermal conductive filler, 50-70 parts of terminal vinyl silicone oil, 10-30 parts of side vinyl silicone oil, 2-14 parts of filler surface treatment agent, 5-14 parts of tackifier, 1-3 parts of colorant, 1-5 parts of platinum catalyst; Component B: 1000-1400 parts of thermal conductive filler, 60-80 parts of vinyl-terminated silicone oil, 5-10 parts of hydrogen-terminated silicone oil, 3-7 parts of hydrogen-terminated silicone oil, 2-14 parts of filler surface treatment agent, 5-14 parts of tackifier, 1-5 parts of inhibitor; The component A and the component B are mixed evenly in a mass ratio of 1:1 for use.

2. The self-adhesive, highly thermally conductive, self-leveling, flame-retardant silicone potting adhesive according to claim 1, characterized in that: The thermal conductive filler has a median particle size of 40 to 80 Spherical alumina, median particle size 6 to 20 Spherical alumina, median particle size 1 to 2 Spherical alumina and median particle size 1 to 5 The aluminum hydroxide is compounded in a mass ratio of 40-80:20-40:10-20:10-20.

3. The self-adhesive, highly thermally conductive, self-leveling, flame-retardant silicone potting adhesive according to claim 1, characterized in that: The filler surface treatment agent has a structure as shown in formula (I): Formula (I) In the above formula (I), R1 is , , , , One of; R2 is one of methyl, methoxy and ethoxy; R3 is methyl or ethyl; R4 is one of methyl, methoxy and ethoxy; In formula (I), n=10 to 200 and is an integer.

4. A self-adhesive, highly thermally conductive, self-leveling, flame-retardant organic silicone potting adhesive according to claim 1 or 3, characterized in that: The filler surface treatment agent is prepared by the following method, and the specific steps are as follows: A. Add hexamethylcyclotrisiloxane monomer, initiator and toluene into a reaction bottle and mix well, add toluene solution of organic base, and stir at room temperature for polymerization reaction for 1 to 6 hours under nitrogen atmosphere; B. Add chlorosilane and acid binding agent to the system after polymerization in step A to carry out end-capping reaction, continue stirring for 1 to 20 hours under nitrogen atmosphere, and then remove the precipitate and filter to obtain the filler surface treatment agent; In step A, The initiator is any substance with the following structural formula: , , , , ; The organic base is selected from any one of the following substances: , , , , , , , ; In step B, The chlorosilane is selected from any one of the following substances: , , , ; The acid binding agent is selected from one or more of triethylamine, pyridine and N,N-diisopropylethylamine.

5. The self-adhesive, highly thermally conductive, self-leveling, flame-retardant silicone potting adhesive according to claim 1, characterized in that: The tackifier has a structure as shown in formula (II): Formula (II) In the above formula (II), R1, R2, and R3 are any of the following substances: , , , , , , , , , , , , , , or .

6. A self-adhesive, highly thermally conductive, self-leveling, flame-retardant organic silicone potting adhesive according to claim 1 or 5, characterized in that: The tackifier is synthesized by hydrosilylation reaction, Michael addition reaction and phosphine hydrogen addition reaction, and the specific steps are as follows: Step 1: pentaerythritol tetraacrylate and a silicon hydrogen compound and a platinum catalyst supported on an alumina carrier are uniformly mixed, and reacted at 80° C. for 5 hours. After the reaction is completed, the mixture is cooled to room temperature, and the supported platinum catalyst is removed by suction to obtain an intermediate compound; Step 2: After the intermediate compound is uniformly mixed with mercaptosilane coupling agent, aminosilane coupling agent, diphenylphosphine and toluene, the mixture is reacted at 40° C. for 12 hours. After the reaction is completed, the mixture is cooled to room temperature and low-boiling substances are removed by vacuum distillation to obtain a tackifier.

7. The self-adhesive, highly thermally conductive, self-leveling, flame-retardant silicone potting adhesive according to claim 6, characterized in that: In step 1, The silicon-hydrogen compound is any substance having the following structure: , , , , , , , , ; In step 2, The mercaptosilane coupling agent is any one or two substances having the following structures: , ; The aminosilane coupling agent is any one or more substances having the following structures: , , , ; The molar ratio of the pentaerythritol tetraacrylate to the silicon-hydrogen compound, the mercaptosilane coupling agent, the aminosilane coupling agent, and the diphenylphosphine oxide is 1: 1-2.7: 0.1-1: 0.1-1: 0.1-0.

5.

8. The self-adhesive, highly thermally conductive, self-leveling, flame-retardant silicone potting adhesive according to claim 1, characterized in that: The vinyl-terminated silicone oil is a double-terminated vinyl polydimethylsiloxane with a viscosity of 60 to 300 mPa·s; the side vinyl silicone oil is a polydimethylmethylvinylsiloxane with a viscosity of 50 to 200 mPa.s and a vinyl mass content of 3 to 8%; the hydrogen-terminated silicone oil is a double-terminated hydrogen-terminated polydimethylsiloxane with a viscosity of 70 to 200 mPa.s; the side hydrogen-containing silicone oil is a polydimethylmethylhydrogensiloxane with a viscosity of 30 to 260 mPa.s and a hydrogen mass content of 0.15 to 1%.

9. The self-adhesive, highly thermally conductive, self-leveling, flame-retardant silicone potting adhesive according to claim 1, characterized in that: The platinum catalyst is a platinum-alcohol complex or a platinum-vinylsiloxane complex, wherein the effective content of platinum atoms is 2000-10000 ppm; the inhibitor is one or more of 1-ethynyl-1-cyclohexanol, 3,5-dimethyl-1-hexyn-3-ol, 4-phenyl-3-butyn-2-ol, 2-methyl-3-butyn-2-ol, diallyl maleate, tetramethyltetravinylcyclotetrasiloxane, and polydivinyltetramethyldisiloxane.

10. A method for preparing the self-adhesive, highly thermally conductive, self-leveling, flame-retardant organic silicone potting adhesive according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Preparation of component A: Add end vinyl silicone oil, side vinyl silicone oil and filler surface treatment agent into a double planetary power mixer and mix and disperse them evenly, then add thermal conductive filler and stir and disperse them for 2 to 5 hours, then heat to 110 to 140°C under stirring, vacuum and stir for 1 to 2 hours, the vacuum degree is -0.09 MPa, cool to room temperature and fill with nitrogen to break the vacuum to obtain base rubber A; then add tackifier, colorant and platinum catalyst, stir and mix at room temperature for 20 to 60 minutes, and degas for 20 minutes to obtain component A; (2) Preparation of component B: Add end vinyl silicone oil and filler surface treatment agent into a dual planetary power mixer and mix and disperse them evenly, then add thermal conductive filler and stir and disperse them for 2 to 5 hours, then heat to 110 to 140°C while stirring, and stir under vacuum for 1 to 2 hours with a vacuum degree of -0.09 MPa. Cool to room temperature and fill with nitrogen to break the vacuum to obtain base rubber B; then add end hydrogen silicone oil, side hydrogen silicone oil, tackifier and inhibitor, stir and mix at room temperature for 20 to 60 minutes, and degas for 20 minutes to obtain component B.

Citation Information

Patent Citations

  • Halogen-free flame-retardant addition type organosilicon potting compound for electronic appliances

    CN102408869A

  • Addition type heat-conducting anti-settling silicon rubber and preparation method thereof

    CN102675882A

  • Two-component organosilicon pouring sealant and preparation method thereof

    CN106947428A

  • Method for improving sedimentation resistance and dispersity of silica powder in organosilicon pouring sealant

    CN110484025A

  • Polysiloxane terephthalic acid alkenyl ester compound used as anti-settling agent

    CN113698609A

Cited By

  • Open-hole organic silicon foam applied to battery pack and preparation method of open-hole organic silicon foam

    CN120795626A